1988
DOI: 10.1139/y88-192
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between plasma proteins and pulmonary surfactant: surface balance studies

Abstract: The influence of human fibrinogen, alpha-globulin, and albumin on the properties of monolayers of pulmonary surfactant under dynamic compression and expansion has been studied at 37 degrees C. Each of the proteins altered some of the properties of the normal compression and expansion isotherms of surfactant such that characteristics deemed desirable for proper lung function were impaired. The order of potency of these effects was fibrinogen greater than globulin greater than albumin. The proteins (a) decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Pulmonary surfactant is sensitive to functional inhibition by plasma proteins, which invade the alveolar space during acute lung injury 21-24. Among the plasma proteins, albumin,25-30 haemoglobin,31 C-reactive protein,32 and fibrinogen and fibrin monomers27 28 33 34 have proven surfactant inhibitory properties in vitro with the following rank order: fibrin monomer>fibrinogen> haemoglobin>albumin. Fresh frozen plasma was chosen for this study for its strong inhibiting effect.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary surfactant is sensitive to functional inhibition by plasma proteins, which invade the alveolar space during acute lung injury 21-24. Among the plasma proteins, albumin,25-30 haemoglobin,31 C-reactive protein,32 and fibrinogen and fibrin monomers27 28 33 34 have proven surfactant inhibitory properties in vitro with the following rank order: fibrin monomer>fibrinogen> haemoglobin>albumin. Fresh frozen plasma was chosen for this study for its strong inhibiting effect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparatively insignificant collapse plateau also suggests that most of the DPPC molecules were removed before monolayer collapse. In a monolayer study of lung surfactant with plasma proteins, it has been suggested that as plasma proteins left the surface, they carried along surfactant lipids with them (24). Furthermore, in a mixed monolayer study of DPPC with SP-B and SP-C, it has been reported that the squeeze-out of the proteins appeared to be accompanied by the exclusion of DPPC at low compression rates (15).…”
Section: Hysteresis Behavior Of Adsorbed γ -Globulin/spread Dppc Monomentioning
confidence: 99%
“…When the cyclic compressionexpansion isotherms were carried up to very high surface pressures, DPPC collapsed and irreversibly left the interface (11). In addition, the hysteresis isotherms of mixed spread plasma protein/pig lung surfactant monolayers implied that the proteins may leave the interface and carry along surfactant lipids with them (24). Plasma proteins seemed to inhibit lung surfactant function by preventing the phospholipids from adsorbing to the interface, possibly by a competition between the plasma proteins and phospholipids for space at the interface rather than direct molecular interactions between proteins and phospholipids (13,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…A deficiency of surfactant at birth, often due to premature delivery, is responsible for the development of neonatal respiratory distress syndrome (1,3). Inactivation of lung surfactant, perhaps as a result of pulmonary edema, is likely involved in the development of adult respiratory distress syndrome (4)(5)(6)(7). As a consequence of the serious morbidity and mortality of these syndromes, surfactant replacement therapy is being investigated by a number of research groups and is increasingly used in the treatment of premature infants (8).…”
mentioning
confidence: 99%